PENGARUH KEBIASAAN MEROKOK DENGAN PROSES PENYEMBUHAN LUKA PASCAOPERASI DI RSU HAJI MEDAN - Fauzi Alvian Hasibuan; Ery Suhaymi (Stikes Syedza Saintika Padang, 2025)
This study aims to determine the effect of smoking habits on the postoperative wound healing process at RSU Haji Medan. The study used a quantitative analytical design with a cross-sectional study approach. The population was all postoperative patients at RSU Haji Medan in 2024, with a total sampling technique of 37 respondents who met the inclusion criteria. The independent variable was smoking habits classified into light, moderate, and heavy smokers, while the dependent variable was the inflammatory phase of wound healing. Data were obtained through questionnaires and observation sheets, then analyzed using the Chi-square test. The results of this study indicate that smoking habits significantly influence delayed postoperative wound healing. Higher smoking intensity is correlated with an increased risk of delayed wound healing and longer recovery time. Medical education, smoking cessation counseling, and perioperative interventions are needed to minimize complications in smoking patients undergoing surgery.